How do individual politicians affect privatization? Evidence from China - Hong Ru; Kunru Zou (Bank of Finland, Institute for Economies in Transition (BOFIT), 2020)
This paper investigates how politicians' patronage connections affect privatizations in China. The connections to top political leaders (i.e., Central Committee of the Communist Party of China) make local politicians engage more in rent-seeking by selling state-owned enterprises (SOEs) at substantial discounts. These connected local politicians are also more protected in anti-corruption investigations, thus extracting more rents by selling SOE assets at substantial discounts. Consequently, the privatizations conducted by the local politicians with patronage connections achieve significantly lower gains in efficiency and performance. To identify the role of patronage connection in privatization, we use the mandatory retirement age cut-offs of Central Committee members in the regression discontinuity design. We find drops in price discounts of privatization deals and jumps in efficiency for privatized SOEs when local politicians lose connections to Central Committee members around the retirement age cut-offs.
URN:NBN:fi:bof-202009012303
Keywords: D73; G30; L3; 330; patronage connection; rent-seeking; privatization; China